2023
DOI: 10.3390/nu15143172
|View full text |Cite
|
Sign up to set email alerts
|

Are Guideline Recommendations on Supportive Nutrition and Exercise Therapy for Cancer Patients Implemented in Clinical Routine? A National Survey with Real-Life Data

Abstract: Malnutrition and cancer cachexia are highly prevalent comorbidities of cancer, limiting patients’ quality of life and being relevant to prognosis. International and national clinical guidelines recommend supportive nutrition and exercise therapy for cancer patients. However, there is little current epidemiological evidence on the implementation of these guideline recommendations in clinical routine. To close this data gap, a national survey in Germany using an online questionnaire was conducted. There were 261… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Cachexia, sarcopenia, and malnutrition are common concomitants of systemic chemotherapeutic treatment—as opposed to tumor burden itself—with an estimated 20% to 25% of all patients with cancer dying as a result of cancer cachexia 176,177 . Early individualized supportive nutrition therapy and exercise programs can help prevent muscle wasting, but implementation of nutrition guidelines is suboptimal partly because of unestablished roles of who should perform initial and repeated screenings 177 . Nutritional interventions are noted to be most effective before the development of cachexia, but most patients with cancer in a nationwide survey reported that nutrition consultation occurred only after there was an obvious deficiency 177 .…”
Section: The Impact Of Malnutrition In Orthopaedic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Cachexia, sarcopenia, and malnutrition are common concomitants of systemic chemotherapeutic treatment—as opposed to tumor burden itself—with an estimated 20% to 25% of all patients with cancer dying as a result of cancer cachexia 176,177 . Early individualized supportive nutrition therapy and exercise programs can help prevent muscle wasting, but implementation of nutrition guidelines is suboptimal partly because of unestablished roles of who should perform initial and repeated screenings 177 . Nutritional interventions are noted to be most effective before the development of cachexia, but most patients with cancer in a nationwide survey reported that nutrition consultation occurred only after there was an obvious deficiency 177 .…”
Section: The Impact Of Malnutrition In Orthopaedic Surgerymentioning
confidence: 99%
“…Early individualized supportive nutrition therapy and exercise programs can help prevent muscle wasting, but implementation of nutrition guidelines is suboptimal partly because of unestablished roles of who should perform initial and repeated screenings 177 . Nutritional interventions are noted to be most effective before the development of cachexia, but most patients with cancer in a nationwide survey reported that nutrition consultation occurred only after there was an obvious deficiency 177 . Unclear roles in screening and delayed nutrition consultation both highlight the need for early and continued multidisciplinary collaboration with medical oncology and nutrition.…”
Section: The Impact Of Malnutrition In Orthopaedic Surgerymentioning
confidence: 99%
“…Studies have shown that an intervention model combining nutrition and physical exercise is most effective in the pre-cachexia stage and can also enhance immunity, thereby supporting the rehabilitation process of cancer patients. [ 8 , 9 ]…”
Section: Introductionmentioning
confidence: 99%